1998
DOI: 10.1080/15216549800203632
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glycosphingolipids of human head and neck carcinomas with comparison to normal tissue

Abstract: Glycosphingolipids of head and neck carcinomas from six tumor‐bearing patients were analyzed and compared to those of normal tissue from similar areas. The total glycosphingolipid content and the lipid‐bound sialic acid were much higher in carcinomas than in normal tissue. Major neutral glycolipids were glucosylceramide, lactosylceramide, trihexosylceramide and paragloboside. Sulfatides were seen only in extracts from normal tissue which also showed a rather simple ganglioside pattern with #GM3 and GD3 as majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
7
9
0
Order By: Relevance
“…In order to elucidate the reasons for selectivity it is important to specify the factors that influence drug uptake and retention in the tissue. These factors are expected to be connected with the differences observed between normal and tumor tissue, for example pH (5)(6)(7)(8), surface charge (9)(10)(11)(12)(13) density lipoprotein receptors (14,15). Since most photosensitizers used in PDT are porhyrin-type molecules possessing sites of protonation/deprotonation in their molecular structures, it is reasonable to consider pH as one of the most important factors.…”
Section: Introductionmentioning
confidence: 99%
“…In order to elucidate the reasons for selectivity it is important to specify the factors that influence drug uptake and retention in the tissue. These factors are expected to be connected with the differences observed between normal and tumor tissue, for example pH (5)(6)(7)(8), surface charge (9)(10)(11)(12)(13) density lipoprotein receptors (14,15). Since most photosensitizers used in PDT are porhyrin-type molecules possessing sites of protonation/deprotonation in their molecular structures, it is reasonable to consider pH as one of the most important factors.…”
Section: Introductionmentioning
confidence: 99%
“…SCC of the upper aerodigestive tract is one of the leading causes of death worldwide. Previously it was demonstrated that the sera of patients with head and neck carcinomas show tumor-size-dependent elevations of serum gangliosides [27]. In view of the role of glycosylation inhibitors, it was postulated that chemical manipulation of glycosylation can be a useful therapeutic strategy for successful chemotherapy against head and neck cancer [28].…”
mentioning
confidence: 99%
“…The only two articles, of the same group, that assessed GSL expression in carcinoma cells compared to head and neck normal tissue, leave doubts as to the histological type and the anatomic sites of the tumors studied; besides, the small number of tumors studied by this group, six cases only, do not correctly represent SCC GSL expression 21,22 . Another description of SCC GSL expression profile was carried out when they studied GSL expression during the differentiation process in SCC cells in the retromolar region 20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, as far as head and neck SCC (squamous cell carcinoma), especially in upper airways and digestive tracts, there are few papers showing GSL expression in the SCC differentiation or malignant transformation, despite the fact that one of the first antibodies developed against GSL be able to identify SCC LacCer 1,15 . Only Bolot et al (1998Bolot et al ( , 1999 assessed GSL expression in head and neck carcinoma and normal tissue cells, notwithstanding these papers leave doubts in regards of histologic types and the anatomical sites of the tumors studied.…”
Section: Introductionmentioning
confidence: 99%